Electrical performance of zinc oxide varistor using powders processed by different latex binders - Karim, A.N. Mustafizul; Begum, Shahida; Hashmi, M. S. J (2005)
The critical electrical parameters such as I-V characteristics, watt-loss and energy absorption capability etc. are the determinants for performance evaluation of ZnO varistors. In this regard there are a large number of contributing variables. Selection of proper binder in the processing of electro-ceramic powder is also a crucial factor. It imparts green strength, enhances compressibility and reduces density gradient within the green discs. Grain growth during sintering and subsequent microstructure of the varistor is also highly influenced by the binder system. It is envisaged that a disc with higher mechanical strength could be capable of withstanding more thermal stress due to temperature gradients. The energy absorption capability as well as high current performance can thus be enhanced. It was possible to generate varistor discs from the powder processed by the latex binder with better electrical performance than that of the powder processed with conventional binder of polyvinyl alcohol. Factorial analysis showed that the level of binder and solid concentration in the slurry had great influence on the energy absorption capability of ZnO varistor.